Medullary thymic epithelial cells and CD8α+ dendritic cells coordinately regulate central tolerance but CD8α+ cells are dispensable for thymic regulatory T cell production. (December 2016) - Herbin, Olivier; Bonito, Anthony J.; Jeong, Seihwan; Weinstein, Erica G.; Rahman, Adeeb H.; Xiong, Huabao; Merad, Miriam; Alexandropoulos, Konstantina
Abstract: In the thymus, antigen presenting cells (APCs) namely, medullary thymic epithelial cells (mTECs) and thymic dendritic cells (tDCs) regulate T cell tolerance through elimination of autoreactive T cells and production of thymic T regulatory (tTreg) cells. How the different APCs in the thymus share the burden of tolerazing the emerging T cell repertoire remains unclear. For example, while mutations that inhibit mTEC development or function associate with peripheral autoimmunity, the role of tDCs in organ-specific autoimmunity and tTreg cell production remains controversial. In this report we used mice depleted of mTECs and/or CD8α + DCs, to examine the contributions of these cell populations in thymic tolerance. We found that while mice depleted of CD8α + DCs or mTECs were normal or developed liver inflammation respectively, combined depletion of mTECs and CD8α + DCs resulted in overt peripheral autoimmunity. The autoimmune manifestations in mice depleted of both mTECs and CD8α + cDCs associated with increased percentages of CD4 + and CD8 + T cells in the thymus. In contrast, while mTEC depletion resulted in reduced percentages of tTreg cells, no additional effect was observed when CD8α + DCs were also depleted. These results reveal that: 1) mTECs and CD8α + DCs cooperatively safeguard against peripheral autoimmunity through thymic T cell deletion; 2) CD8α + DCs are dispensable for tTreg cell production, whereas mTECs play a non-redundant role in this process; 3) mTECs and CD8α + DCs make unique contributions to tolerance induction that cannot be compensated for by other thymic APCs such as migratory SIRPα + or plasmacytoid DCs. Graphical abstract: Highlights: Depletion of mTECs and CD8α + DCs leads to overt autoimmunity. mTECs and CD8α + DCs cooperatively regulate thymocyte deletion. CD8α + DCs do not play a quantitative role in thymic Treg production.